A study of parametric effects on thermal profile of submerged arc welding process - Sarkar, Abhijit; Rai, R.N.; Saha, S.C. (Journal of Naval Architecture and Marine Engineering, 2015)
In this study, a Numerical model is carried out to study the effect of welding parameters on the temperature variations in Submerged Arc Welding process (SAW) with moving heat source model (Gaussian distribution) by using finite difference method (FDM). The proposed method is validated from the experimental results and found is in good agreement with results obtained by experimental. The mathematical model of transient thermal is also recognized to simulate Peak temperature. Finally Parametric effects on temperature profiles based on numerical results, are carried out for different weld parameters including welding speed, heat input, and plate thickness. It has been shown that all those parameters are playing an essential role in affecting the temperature distribution.